Dynamic Contrast-Enhanced Ultrasound Identifies Microcirculatory Alterations in Sepsis-Induced Acute Kidney Injury. Issue 8 (August 2018) - Lima, Alexandre; van Rooij, Tom; Ergin, Bulent; Sorelli, Michele; Ince, Yasin; Specht, Patricia A. C.; Mik, Egbert G.; Bocchi, Leonardo; Kooiman, Klazina; de Jong, Nico; Ince, Can
Abstract : Objectives: We developed quantitative methods to analyze microbubble kinetics based on renal contrast-enhanced ultrasound imaging combined with measurements of sublingual microcirculation on a fixed area to quantify early microvascular alterations in sepsis-induced acute kidney injury. Design: Prospective controlled animal experiment study. Setting: Hospital-affiliated animal research institution. Subjects: Fifteen female pigs. Interventions: The animals were instrumented with a renal artery flow probe after surgically exposing the kidney. Nine animals were given IV infusion of lipopolysaccharide to induce septic shock, and six were used as controls. Measurements and Main Results: Contrast-enhanced ultrasound imaging was performed on the kidney before, during, and after having induced shock. Sublingual microcirculation was measured continuously using the Cytocam on the same spot. Contrast-enhanced ultrasound effectively allowed us to develop new analytical methods to measure dynamic variations in renal microvascular perfusion during shock and resuscitation. Renal microvascular hypoperfusion was quantified by decreased peak enhancement and an increased ratio of the final plateau intensity to peak enhancement. Reduced intrarenal blood flow could be estimated by measuring the microbubble transit times between the interlobar arteries and capillary vessels in the renal cortex. Sublingual microcirculation measured using the Cytocam in a fixed area showed decreased functional capillary density associated with plugged sublingual capillary vessels that persisted during and after fluid resuscitation. Conclusions: In our lipopolysaccharide model, with resuscitation targeted at blood pressure, contrast-enhanced ultrasound imaging can identify renal microvascular alterations by showing prolonged contrast enhancement in microcirculation during shock, worsened by resuscitation with fluids. Concomitant analysis of sublingual microcirculation mirrored those observed in the renal microcirculation. Abstract : Supplemental Digital Content is available in the text.